ANALISIS KEMAMPUAN SPASIAL VISUALIZATION SISWA SEKOLAH DASAR DALAM PEMECAHAN MASALAH GEOMETRI - Amalia Ainurrahmah; Griet Helena; Rukmini Handayani (STKIP Subang, 2023)
Spatial Visualization ability is related to geometry and has the ability to visualize spatial displacements and helps students to solve problems correctly. In solving geometric problems is the ability to solve problems by mastering the rules and concepts of geometry. This study aims to identify and analyze the lack of spatial ability which was carried out to analyze how the Spatial Visualization ability is applied to solving geometry problems for fourth grade students at Alam Islam Talasia School, Bogor City. This development uses a qualitative method. with a descriptive approach. This research begins with collecting various information needs, making observation grids, making research instruments, validating by experts, then carrying out data collection, and analyzing the results of the data obtained. The results of the study stated that there were students who did not yet have spatial visualization abilities and there were also students who had spatial visualization abilities, as well as several influencing factors.